Impact of Third-Party Enforcement of Contracts in Agricultural Markets – A Field Experiment in Vietnam - Christoph Saenger; Maximo Torero; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
We study the effect of alleviating information asymmetry regarding product quality that is widespread in developing-country agricultural markets. Opportunistic buyers may underreport quality levels back to farmers to reduce the price they have to pay. In response, farmers may curb investment, negatively affecting farm productivity. In an experiment, we entitle randomly selected smallholder dairy farmers in Vietnam to independently verify milk testing results. Treatment farmers use 13 percent more inputs and also increase their output. We show that the buying company had initially not underreported product quality, which is why third-party monitoring led to a Pareto improvement in the supply chain.
Keywords: C93; D86; L14; O13; Q12; Q13; 330; Contract farming; Information asymmetry; Third-party enforcement; Experimental economics; Framed field experiment; Dairy; Agribusiness; Vietnam